Pengaruh Service Quality dan Price Terhadap Customer Satisfaction Pada Satiga Coffee & Resto Kota Padang - Winda Konita Lutfia; Nidia Wulansari (Nawasena: Jurnal Ilmiah Pariwisata, 2024)
This motivation from research are consumer complaints regarding Quality of Service and Price. The research aim is to describe the Quality of Service and Price impact on Satisfaction of Customer at Satiga Coffee & Resto, Padang City. The population for this research is peoples who have made purchases at Satiga Coffee & Resto, Padang City with a all sample of 330 consumers using techniques of purposive sampling. The technique for collection of data uses a questionnaire through a scale of Likert which has been passed validity and reliability test through SPSS version 26.00. The research results are Service Quality with a respondent achievement rate of 75.2%, Price with an achievement rate from respondent is 74% and Customer Satisfaction with an achievement rate from respondent is 74.8%. The Service Quality (X1) and Price (X2) contribution to Customer Satisfaction (Y) is 61.2% when the remaining 38.8% is influenced by other factors